O preconceito como fator de violência: um estudo de caso dos paraenses em Manaus - Tamer, Alexandre dos Santos (2016)
The current study analyzed the relationship between the criminal indicators of the city of Manaus, specifically robbery, theft, homicide and murder after robbery, from March / 2012 to July / 2016, with the number of Paraenses responsible for these indices, thus deconstructing regional prejudice against the Paraense migrants, since it was found that the perpetrators of these crimes were, for the most part, Amazons. The inductive method was used, and interviews, bibliographical and field research were done, enabling a consistent analysis of the data surveyed. Regarding the purposes the research was characterized as qualitative-quantitative